The Influence of Organizational Factors on Counterproductive Work Behaviour (CWB) in Malaysian SMEs - Veeriah, Ravikumar; Khairunnisa, Abdul Aziz; Nurul Ashykin, Abd Aziz (Human Resource Management Academic Research Society (HRMARS), 2023)
Employee’s Counterproductive Work Behavior (CWB) is a negative behavior that employees undertake. Every year, firms all across the world suffer financially and operationally as a result of employee participation in CWB. CWB give an impact on business and these impacts are also more likely to be felt by SMEs also, given their smaller margins and lack of knowledge in overcoming these issues. It is important for SMEs to be able to prevent this counterproductive behavior at work. Hence, this study attempts to examine the influence of organizational factors (organizational support, organizational ethical climate and organizational justice) on CWB among Malaysian SMEs. A quantitative method was used in this study and data was collected from 149 employees from various SMEs employee via online questionnaires. PLS-SEM was used to analyze three (3) hypotheses for this study. The result found that organizational support and organizational justice showed significant and negative influence on CWB, whereas organizational ethical climate did not have any significant influence on CWB. Theoretically, this study provides empirical evidence on the factors that influence CWB. From a practical perspective, the study provides better understanding for SMEs business on the aspects that they should focused in preventing CWB.